The Influence of Ca2+ Ion Addition on Physical Characteristics of Aerobic Granular Sludge in Sequencing Batch Reactor - Anfasha, Nurdian Hari; Handajani, Marisa (Journal of Community Based Environmental Engineering and Management, 2024)
Aerobic Granular Sludge is a collection of microbes that allows for the simultaneous removal of carbon, nitrogen, and phosphorus in one reactor system. The formation of Aerobic Granular Sludge is influenced by many factors, such as the type of carbon source, hydrodynamic shear forces, amount of EPS and up to the presence of diavalent cations. In this study Ca2+ ion was added to the reactor as an additional chemical with the aim of investigating the effect of Ca2+ ion dosage on the physical characteristics of Aerobic Granular Sludge. The objective of this research is to find the influence of Ca2+ ions addition to physical characteristics of aerobic granular sludge. There are 3 (three) reactors as a means to compare, with variations in the addition of Ca2+ ions as much as 20 mg/l, 45 mg/l and 100 mg/l which are entered into artificial domestic wastewater. The results obtained from this study are the physical characteristics of granular in reactor 1 has an average diameter ranging between 1.12 mm - 1.72 mm, with an aspect ratio of 0.71, then in reactor 2 has an average diameter ranging between 1.63 mm - 2.23 mm, with an aspect ratio of 0.8, and Reactor 3 has an average ranging 1.78 mm - 3.14 mm with an aspect ratio of 0.81. SEM analysis conducted showed that reactor 3 showed the presence of more Ca2+ ions than the other reactors. Physical characteristics get better as Ca2+ ions increase.